Pathogenicity of the avian Escherichia coli isolates from pericarditis and femoral head necrosis lesions of the colibacillosis in experimentally infected chicks - MOHSENIFARD, E; BASAKI, M; ASASI, K; SHARIFIYAZDI, H; ABDI-HACHESOO, B (The Indian Journal of Animal Sciences, 2019)
The aim of the present study was to evaluate the relationship between different combinations of seven (ompT, hlyF, iss, iutA, iroN, tsh and cvaC) Colicin V (ColV) plasmid associated virulence genes (VGs) and pathogenicity of avian E. coli isolates. After detection of the different patterns of VGs among 290 E. coli isolates from pericarditis and femoral head necrosis lesions of colibacillosis and the 70 isolates from feces of apparently healthy birds (AFEC), the day-old chick lethality test was conducted. Distribution of genetic patterns was different between the APECs and AFECs isolates, so that 67.3% of the APECs typed were represented by two specific genetic patterns (ompT+/hlyF+/iss+/iutA+/iroN+/tsh+/cvaC+; ompT+/hlyF+/iss+/iutA+/iroN+/tsh+/cvaC-). Furthermore, both the APECs and AFECs isolates with different genetic patterns were lethal for day-old chicks. The ColV plasmid or some of its VGs can provide helpful characteristics to describe APECs. Furthermore, extraintestinal environments may supply requirements for the pathogenicity of the avian E. coli isolates harboring different genetic background. However, further studies are needed to confirm the definite link between avian E. coli isolates pathogenicity and their genotype.